EXPERIMENTAL UNMANNED AERIAL VEHICLE FLIGHT DATA MEASUREMENT AND THEIR POST-PROCESSING ANALYSIS - Kharchenko, Volodymyr; Kuzmenko, Nataliia; Mykhatsky, Oleksiy; Savchenko, Oleksiy (Proceedings of National Aviation University, 2014)
In the article the flight data measurement and transmission to the ground control station for further decoding and post-processing are described. The article demonstrates the developed flight data processing and visualization tool with its operation algorithm. Some possible options of the tool such as trajectory displaying in the three-dimensional coordinates, using Google Earth satellite mapping and arbitrary combining graphs of unmanned aerial vehicles real flight parameters with their explanation were represented.